An Insight into the Direction of Environmental Management in New Zealand's Coal Industry - T Clemens; D Trumm (The Australasian Institute of Mining and Metallurgy, 2004)
Adopting environmentally acceptable practices in New Zealand is a crucial requirement for mineral wealth development. Recent planned expansions in the coal industry have increasingly placed mining in the media spotlight. A lack of appropriate national environmental guidelines has resulted in inconsistent responses and assessments of current and prospective mine sites. Such inconsistencies have lead to delays in decisions on developing economic mineral deposits that may have only minor short-term impacts, and have also allowed unacceptable environmental management practices to continue elsewhere.   A research collaboration between CRL Energy, Landcare Research, University of Canterbury and University of Otago aims to provide regulator groups and the mining industry with a unified approach to the requirements of the Resource Management Act 1991, which is the legislation that predominantly drives the nationÆs environmental policies and guidelines. The tangible outcome of this research programme will be guidelines for an integrated decision-making framework based upon robust multidisciplinary science. The result of this unified process will facilitate the development of viable mineral deposits and prevent excessive environmental impacts.   The framework will be derived from a synthesis of four objectives. Objective 1 identifies potential water quality impact. This objective is based on a targeted geochemical study of the lithology and waterways of the West Coast and Southland. Objective 2 categorises the degree of impacts on the ecology of receiving aquatic ecosystems and determines the processes that drive aquatic ecosystem recovery. Objective 3 identifies best strategies to sufficiently manage impacted ecosystems, and to prevent future unacceptable impacts. Objective 4 combines the findings of Objectives 1 - 3 into a standard decision-making framework. The development of this framework development will include wide consultation with representatives of the mining industry and regulator groups. It is anticipated that this multidisciplinary approach will provide a robust and coherent, standardised system that will assist in achieving industry and environmental targets.